FUENTES DE INVESTIGACIÓN: LAS BASES DE DATOS ESPECIALIZADAS - Fairlie Frisancho, Ebor (2005)
This article tries to provide enough information given by the Internet for teacher´s research. Besides we are presenting the use of the Internet at San Marcos University with respect to other institutions.